SAGEmap: A Public Gene Expression Resource - Lash, Alex E.; Tolstoshev, Carolyn M.; Wagner, Lukas; Schuler, Gregory D.; Strausberg, Robert L.; Riggins, Gregory J.; Altschul, Stephen F. (Genome Research, 2000)
We have constructed a public gene expression data repository and online data access and analysis, WWW and FTP sites for serial analysis of gene expression (SAGE) data. The WWW and FTP components of this resource, SAGEmap, are located at http://www.ncbi.nlm.nih.gov/sage andftp://ncbi.nlm.nih.gov/pub/sage, respectively. We herein describe SAGE data submission procedures, the construction and characteristics of SAGE tags to gene assignments, the derivation and use of a novel statistical test designed specifically for differential-type analyses of SAGE data, and the organization and use of this resource.